A Priestia megaterium MF3 with high-efficiency zearalenone degradation: functional genomic insights and mechanistic exploration - Meng, Di; Xu, Kai-Zhong; Hou, Hong-Jian; Liu, Jin-Bin; Deng, Dan-Dan; Li, Jun-Min; Fang, Ya-Kun; Zhu, Xiao-Qin; Pei, Dong-Li (Frontiers in Microbiology, 2025)
Zearalenone (ZEN), a mycotoxin produced by Fusarium species, is widely distributed and poses significant health risks to both animals and humans due to its toxic effects. In this study, a Priestia megaterium MF3, exhibiting high ZEN degradation capacity, was identified through comprehensive morphological, physicochemical, 16S rRNA gene sequencing, and whole-genome sequencing analyses. Strain MF3 reached its peak ZEN degradation rate in BHI medium (pH 7, 30°C), with > 90% efficiency maintained across 24–72 h, 1–5% inoculum, and 10–40 μg/mL ZEN. The ZEN-degrading activity of strain MF3 was attributed to both extracellular and intracellular components, with extracellular enzymes in the fermentation supernatant playing a predominant role. LC-MS analysis identified key ZEN degradation products, including 1-(3,5-dihydroxyphenyl)-6’-hydroxy-1’-undecen-10’-one, ZEN-P, and zearalanone. Whole-genome sequencing further revealed the presence of genes encoding α/β hydrolases and phosphotransferases, which are likely involved in the hydrolysis and phosphorylation of ZEN. Furthermore, strain MF3 demonstrated an impressive ability to remove 81.78% of ZEN from moldy corn within 12 h. This study not only identifies a highly efficient bacterial strain for ZEN biodegradation but also provides valuable insights into its degradation mechanism, offering potential applications for mycotoxin detoxification in the food and feed industries.